Mean Subpubic Angle of Patients Visiting Department of Radiodiagnosis of a Tertiary Care Hospital: A Descriptive Cross-sectional Study - Ruku Pandit; Aarati Adhikari; Hari Prasad Upadhyay (Journal of Nepal Medical Association, 2022)
Introduction: The subpubic angle in the pelvis is most often used to estimate the sex with a higher degree of accuracy. Despite the anthropological and obstetric importance of the subpubic angle, only a few studies exist in the Nepalese population. The objective of this study was to determine the mean subpubic angle of the patient visiting the department of radiodiagnosis of tertiary care hospital.